If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3y + 7x + 5y = 0 Reorder the terms: 4x + 7x + -3y + 5y = 0 Combine like terms: 4x + 7x = 11x 11x + -3y + 5y = 0 Combine like terms: -3y + 5y = 2y 11x + 2y = 0 Solving 11x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 11x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 11x + 0 = 0 + -2y 11x = 0 + -2y Remove the zero: 11x = -2y Divide each side by '11'. x = -0.1818181818y Simplifying x = -0.1818181818y
| 105=x^2+16x | | 62+5=4z-7 | | 5=-4b-8 | | 3p+4p-2=12 | | -(2x-5)=2(x+2)+3x | | 2+u=4 | | -3f-1=8-3f | | 5=2y^2+2y | | 4=-8f+5 | | 6x+3x+5+7=48 | | 2/3x-14=22 | | x=2x+x^2 | | 72+5x-8+6x+6=180 | | 7a+6=-24 | | 3x-12-4x=6+5x | | 7+r=9 | | 9(x+6)+2(x+6)=7x-7 | | 9x-12y=8 | | 6(2c+10)=5(c+5) | | 4n^2-7=-7n | | 30/20=x/4 | | 5c+9=4z-1 | | 3+4(x-5)=34 | | 9(x+1)+4(x+1)=6x-6 | | -6+11=-5-2 | | x^7-6x^5+2x^4-5=0 | | 2p-3=11 | | 3+7n=1+6n | | ln^3x=5 | | 5k^2=6-k | | (x+1)+(y-2)=7 | | 4x+25=8x+37 |